The psychosocial needs of next of kin of ventilated patients admitted to intensive care unit, Hospital Universiti Sains Malaysia - Dharmalingam, T. Kumaravadivel (2017)
Background: The needs of intensive care patient’s family members are often neglected. The present study aimed to perform factorial validation and establish psychometric properties of Malay translated Critical Care Family Need Inventory (CCFNI-M) and also the needs of families of intensive care unit patients in Malaysia as perceived by family members. Methods: This cross-sectional survey was conducted among family members of Intensive Care Unit of Hospital Universiti Sains Malaysia, Malaysia. Validation study consisted of four protocols: Forward-Backward translation, validity, internal reliability and inter domain correlations phases. This Malay validated Critical Care Family Needs Inventory then was used to identify the family needs among the respondents. Descriptive statistics as well as mean comparison analyses were employed to achieve the aim of the present study. Results: Preliminary analyses reported the suitability of data for factorial validation. With reference to the original CCFNI, five factors were extracted which explained 49.4% of the total variance. After removal of several items for different reasons, the final items in CCFNIM were 42. The internal consistency values for five dimensions ranged from 0.72 to 0.87 with inter domain correlation values (r) among the dimensions ranged between 0.36 and 0.61. The findings showed that family members ranked Assurance items as the most important needs. In terms of subscales scores, Assurance and Information evidenced higher mean scores compared to other dimensions. All the family need dimensions had positive and significant associations with one another. The highest correlation was noted among Comfort – Support pair, r(58) = 0.73, p < 0.001. No significant differences in the mean values found across gender, history of admission and types of relationships. In contrast, significant mean difference was observed across level of education. Conclusion: The high measures of factorial validity, internal consistency and inter domain correlations values of the CCFNI-M make it as a suitable measure for assessing the familyneeds of critical care patients. Identifying the needs of family members in the intensive care unit is imperative as it raises awareness and contributes knowledge in terms of family needs to healthcare providers, policy makers, medical social workers and general public.